Massificação da consultoria: descrição e análise dos processos de mudança do SEBRAE-SP - Silveira, Frederico Zenorini da (2007)
In the whole world, the economical changes, incremented by the information tecnology´s advance and by the pouplarization of basic manegement methods, associeted to the desindustrialization process and to the expansion of the service field, made that the small firms have become the highlights in the economy of several countries, being responsable for a large part of the employment and profits. In that context, this study intend to contribute with the understanding of the growing process of the brazilian consultant field, its acting forms and its relationship with the other organizations. Particularly, analysing the SEBRAE-SP´s acting form, with a parallel between its goals and its posicional manners in the face of other organizations. That is why, it is necessary to comprehend how much that ocurried changes in the acting forms of the institution in the past few decads, are a reflexion of a new form of interaction with the management consultant field.